Karakteristik Organoleptik Gula Kelapa Serbuk dengan Penambahan Gum Arab sebagai Pengawet Nira pada Saat Penyadapan - Anisya Jasmin Zahrani; Dwi Raharjo; Lucky Hartanti (Program Studi Teknologi Hasil Pertanian, 2026)
This study aimed to determine the effect of adding gum arabic as a natural preservative to coconut sap during tapping on the organoleptic characteristics of coconut sugar powder. Coconut sap is highly susceptible to fermentation due to microbial activity, which can reduce the sensory quality of the final product. Therefore, the use of gum arabic with antimicrobial properties is expected to maintain sap quality and improve the sensory attributes of coconut sugar powder. This study employed a Randomized Block Design (RAK) with a single factor, namely gum arabic concentration (0; 0.5; 1.0; 1.5; 2.0; and 2.5 g/L coconut sap) with four replications. The observed organoleptic parameters included color, aroma, taste, and overall acceptability. Data were analyzed using the Kruskal–Wallis test at a 5% significance level. The results showed that the addition of gum arabic had no significant effect on aroma, but significantly affected color, taste, and overall acceptability. Increasing gum arabic concentration tended to produce a browner color, sweeter taste, and higher panelist preference. The best treatment was obtained gum arabic at 2 g/L coconut sap, resulting in brown color, typical coconut sugar aroma, sweeter taste, and the highest overall acceptability.